3 RATE OF UNDIAGNOSED COGNITIVE IMPAIRMENT IN COMMUNITY SETTINGS: IS THERE A NEED FOR SCREENING?. (1st March 2007) - Baker, D.; Yasui, N.; Lane, N. J.; Ohrt, T. L.; Asthana, S.; Gleason, C E
Abstract : The Midwest Initiative for Dementia Screening (MINDS) Project, funded by Extendicare Foundation, proposed to improve early detection of previously undiagnosed cognitive impairment in community-dwelling individuals through memory screenings and educational lectures. Our goals were first to assess the rate of undiagnosed cognitive impairment and to provide appropriate referral information for individuals in need of further evaluation. The community screenings were not intended to provide diagnoses but rather to identify individuals in need of a clinical evaluation. Still, participants with limited access to neuropsychological services were provided with a summary of screening data sufficiently extensive to serve the purpose of a clinical evaluation. The data could be used by a primary care provider (PCP) within the context of a comprehensive clinical diagnostic evaluation. We provided memory screenings for 260 individuals, screened at one of eight locations around southern Wisconsin. Of those screened, 203 (78%) were women with a mean age of 77 years. Male participants had a mean age of 83 years. Of the 260 individuals screened, 129 (50%) showed no evidence of cognitive impairment, scoring at or above the normal range on cognitive tests. Testing also confirmed a previous diagnosis of a memory disorder for 24 individuals (9%). The remaining 107 (41%) individuals demonstrated varying degrees of cognitive impairment on testing, presumably undetected. Performance on screening tests was considered with medical history and current medications. Based on the totality of information gathered, we suspected that 35 individuals demonstrated cognitive impairments in multiple cognitive domains and that the deficits were not adequately explained by other medical conditions or concurrent treatments. These individuals (33% of the 107) subsequently received a recommendation for a full diagnostic workup to determine if their screening performances were the result of a neurodegenerative disease such as Alzheimer's dementia. The 30 individuals (28% of the 107) demonstrating focal memory impairment on screening measures, not attributed to other medical conditions or treatments, were referred for further evaluation to assess for a mild cognitive impairment. The remaining 42 (39%) were encouraged to discuss issues such as medications, depression, and anxiety with their PCP and monitor their condition. We also compared the Mini Mental Status Exam (MMSE) scores of all participants with the results of their full memory screening performance. A score of 24 or lower on the MMSE was considered impaired. Of the 260 participants, 21 (8%) scored in the impaired range on the MMSE. Twelve of those participants had their memory disorder confirmed by our testing, leaving 9 of the remaining 248 participants (4%) scoring in the impaired range. PCPs often rely on a MMSE to quickly gauge the cognitive functioning of patients and alert them to impairment. However, our findings indicate that only 8 individuals (7%) of the 107 suspected here to have cognitive impairment demonstrated impairment on the MMSE. In other words, the cognitive decline in 93% of the participants who demonstrated impairment on our testing would have gone unnoticed if the MMSE was relied on as the sole screening method. The MINDS project revealed that older adults residing in the community are indeed interested in participating in memory screenings. Consistent with previous reports, nearly half demonstrated some level of cognitive impairment, warranting follow-up evaluation. Furthermore, data gathered in similar screenings could be used by PCP in communities where there is limited access to neuropsychological services, reducing reliance on the MMSE as the only tool to assess cognition.